(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, it is defined the affairs of register of the population in Uzbekistan SSR (Soviet Socialist Republic) in 1926. In addition, Soviet Union’s purposes is determined widely which is from register of the population. In 1926, the population of the Turkistan is registered and Central Statistical Committee formed population’s statistics. The final results of the register of the population are analyzed respectively through the published main statistic sources which are regions’ sections. Through the conclusion of the register of the population the economical, social, and political life is planned to the next decades in this place. As well as, through the final results of the affairs of register of the population, the number of total population and national content of the regions’ sections are listed. In the article, the process to prepare of the register of the population and its many shortcomings has been revealed and given the scientific conclusions.